Thiopurine-induced toxicity is associated with dysfunction variant of the human molybdenum cofactor sulfurase gene (xanthinuria type II) - Stiburkova, Blanka; Pavelcova, Katerina; Petru, Lenka; Krijt, Jakub (Toxicology and applied pharmacology, 2018)
BACKGROUND: The aim of our study was to identify the genetic background of thiopurine-induced toxicity in a patient with a wild-type thiopurine methyltransferase genotype and activity. A 38-year-old Caucasian woman presented with cutaneous necrotizing vasculitis pancytopenia one month after starting azathioprine therapy. METHODS: During a routine biochemical follow-up of the patient, undetectable serum uric acid (<10 μl) was observed. A high performance liquid chromatography analysis of urinary purines revealed increased levels of xanthine (137 mmol/mol creatinine). The suspected diagnosis of hereditary xanthinuria, a rare autosomal recessive disorder of the last two steps of purine metabolism, was confirmed by sequence analysis. RESULTS: An analysis of XDH/XO and AOX1 revealed common polymorphisms, while analysis of the MOCOS gene identified a rare homozygous variant c.362C > T. Dysfunction of this variant was confirmed by significantly decreased xanthine dehydrogenase/oxidase activity in the patient's plasma (<2% of control mean activity). CONCLUSIONS: We present a biochemical, enzymatic, and molecular genetic case study suggesting an important association between a hitherto undescribed dysfunction variant in the MOCOS gene and thiopurine-induced toxicity. The identified variant c.362C > T results in slower thiopurine metabolism caused by inhibition of 6-mercaptopurine oxidation (catabolism) to 6-thioxanthine and 6-thiouric acid, which increases the formation of the nucleotide 6-thioguanine, which is toxic. This is the first clinical case to identify the crucial role of the MOCOS gene in thiopurine intolerance and confirm the impact of genetic variability of purine enzymes on different therapeutic outcomes in patients undergoing thiopurine treatment.
Keywords: Mercaptopurine; sulfurtransferasy; Xanthine Dehydrogenase; polymorfismus genetický; Uric Acid; Humans; lidé; Methyltransferases; Purine-Pyrimidine Metabolism, Inborn Errors; xanthinoxidasa; merkaptopurin; poruchy metabolismu purinů a pyrimidinů; kyselina močová; xanthindehydrogenasa; Female; methyltransferasy; Adult; xanthin; Polymorphism, Genetic; Xanthine Oxidase; Sulfurtransferases; ženské pohlaví; aldehydoxidasa; dospělí; Xanthine; Aldehyde Oxidase